PROGRAM GURU TAMU BAGI SISWA-SISWI KELAS 6 SD X-TANGERANG - Dadi, Kanisius Komsiah; Siregar, Rahul Ericson (CREDENDUM: Jurnal Pendidikan Agama, 2022)
This study aims to (1) describe the “Guest Teacher” program in X-School of Tangerang, (2) describe students’, Parents’, and Teachers’ understanding of and support of The Guest Teacher Program. Respondents in this study were students, teachers and parents who participated in the Guest Teacher program. Data collection techniques in this study used interviews, observation, and documentation. This research employs the descriptive qualitative approach. The results showed that the guest teacher program, which is implemented by X-School of Tangerang for 6th graders, is 1st aimed at creating a web building between the school, alumni, and parents. 2nd the aim of this program is to a school promotion media. This program has impacted students’ attitudes.